DIAGNOSIS OF VITICULTURE POTENTIAL IN ROMANIA - Boboc Dan; Ladaru Georgiana-Raluca (Ekonomika Poljoprivrede (1979), 2012)
This research investigates Romanian viticulture potential. In pursuing this, statistical data were analyzed, related to the areas occupied by vines and grape production per hectare of the Romanian and European Union vineyard. Romania is among the countries with a millenary tradition in vines. Climatic and soil conditions of our country are favorable for growth and fruiting vines.